Copper Corrosion by Atmospheric Pollutants in the Electronics Industry. (2nd October 2013) - Valdez Salas, Benjamin; Schorr Wiener, Michael; Zlatev Koytchev, Roumen; López Badilla, Gustavo; Ramos Irigoyen, Rogelio; Carrillo Beltrán, Monica; Radnev Nedev, Nicola; Curiel Alvarez, Mario; Rosas Gonzalez, Navor; Bastidas Rull, Jose María
Abstract : Hydrogen sulphide (H2 S) is considered one of the most corrosive atmospheric pollutants. It is a weak, diprotic, reducing acid, readily soluble in water and dispersed into the air by winds when emitted from natural, industrial, and anthropogenic sources. It is a pollutant with a high level of toxicity impairing human health and the environment quality. It attacks copper forming thin films of metallic sulphides or dendrite whiskers, which are cathodic to the metal substrate, enhancing corrosion. H2 S is actively involved in microbially influenced corrosion (MIC) which develops in water, involving sulphur based bacteria, in oxidizing and reducing chemical reactions. H2 S is found in concentrated geothermal brines, in the atmosphere of geothermal fields, and in municipal sewage systems. Other active atmospheric pollutants include SO X, NO X, and CO. This investigation reports on the effects of H2 S on copper in microelectronic components of equipment and devices, with the formation of nonconductive films that lead to electrical failures.